A place branding framework for tourism based on visual urban perception in Yinchuan City, Ningxia Hui Autonomous Region, China - Ji, Guangyao (2024)
This thesis investigates the development of tourism in the Ningxia Hui Autonomous Region of China, with a particular focus on its capital city, Yinchuan. It explores the specific relationships between city image, place branding, visual urban perception, and the ‘All-for-One Tourism’ policy in China. The literature review begins by emphasizing the critical role of city image and place branding in shaping tourism. It then delves into issues related to visual urban perception before examining the role of the ‘All-for-One Tourism’ policy on Ningxia’s tourism development. As urbanization progresses, place branding has become a crucial tool for enhancing city competitiveness. With its natural beauty, architectural treasures, and cultural diversity, Ningxia has benefited from the Chinese government’s ‘All-for-One Tourism’ policy, which aims to promote its tourism industry. Against this backdrop, the study introduces a novel approach by integrating visual urban perception into place branding to enhance tourism in Ningxia, particularly in Yinchuan city. The study outlines three main research objectives: identifying unique local characteristics, integrating visual urban perception paradigms, and proposing a place branding framework. To address these objectives, the research methodology begins with a detailed research design and justification for focusing on Yinchuan as a case study. The methodology then discusses data collection methods, including expert interviews and a questionnaire survey. Expert interviews identify key elements of Yinchuan’s place identity, such as visual landmarks, cultural connotations, media strategies, and potential improvements. These insights inform a subsequent questionnaire survey that explores the relationship between visual urban perception and place identity. A mixedmethod approach is employed, combining expert interviews with 23 experts from various professional backgrounds and a random sampling questionnaire survey among 400 residents and tourists of Yinchuan. The survey results are analyzed quantitatively through statistical comparative analyses and qualitatively through thematic analysis. The results are structured around key analytical themes, revealing respondents’ preferences and perceptions regarding Yinchuan’s place branding elements, thereby contributing to a comprehensive understanding of visual urban perception and place identity. The findings from both expert interviews and public surveys inform the proposed place branding framework for Yinchuan based on five key attributes: visual landmarks, visual cultural connotations, visual media strategies, potential improvements, and future visual landmarks. This framework offers innovative perspectives and practical implications for Ningxia’s tourism industry. From this perspective, the study leverages visual urban perception to construct a place branding framework that enhances tourism and significantly contributes to the nationwide effort to boost the tourism economy. Furthermore, it serves as a catalyst for future research into innovative place branding frameworks for underdeveloped regions and lesser-known cities across mainland China.